Loyal or habitual? exploring differences of loyalty and habits for FMCG brands in Turkey - Efendioğlu, Ebru. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2023., 2023)
This dissertation is an exploration of the brand loyalty and habitual behavior of consumers in Turkey when it comes to fast- moving consumer goods (FMCG) brands in the personal care industry. The literature on habitual behavior and brand loyalty, with a specific focus on attitudinal loyalty, has separate studies on these topics that significantly affect consumer behavior, however, few studies examine their associations. Therefore, this paper aims to address this gap by concentrating on both concepts as a whole. Moreover, due to its economic standpoint and changing consumer attitudes, Turkey provides an intriguing environment to conduct this research. The study examines Turkish consumers’ habits and loyalties by utilizing a qualitative research method through a research design of in-depth interviews. The findings were categorized around ten themes which were subjected to thematic analysis and analyzed individually. The analysis revealed that there are five main habitual behaviors that consumers in Turkey utilize, consciously or subconsciously, when shopping for or consuming personal care brands, such as familiarity, price sensitivity, ease of accessibility, prior research, and advertising and marketing efforts. The study suggests that while personal care consumers in Turkey still regard brands highly, their decisions are largely influenced by habits which aid in consumers making decisions more quickly and ensuring satisfaction.
Keywords: Consumer goods -- Turkey.; Brand loyalty.